2007
DOI: 10.1007/s10641-007-9216-7
|View full text |Cite
|
Sign up to set email alerts
|

Food borne parasites as indicators of trophic segregation between Arctic charr and brown trout

Abstract: The habitat and diet choice and the infection (prevalence and abundance) of trophically transmitted parasites were compared in Arctic charr and brown trout living sympatrically in two lakes in northern Norway. Arctic charr were found in all main lake habitats, whereas the brown trout were almost exclusively found in the littoral zone. In both lakes the parasite fauna reflected the niche segregation between trout and charr. Surface insects were most common in the diet of trout, but transmit few parasites, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 32 publications
4
66
1
Order By: Relevance
“…For large-sized fish the diet overlap is even lower as the charr predominantly feed on G. lacustris, whereas the trout mainly prey upon small Arctic charr. Gammarus is an important macroinvertebrate prey for many fish species (MacNeil et al 1999), but it is also an important intermediate host for several parasite species, including the cestode Cyathocephalus truncatus that can parasitize both Arctic charr and brown trout (Amundsen et al 2003;Knudsen et al 2008). This cestode can manipulate the behaviour of their Gammarus hosts in order to increase transmission rates (Knudsen et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For large-sized fish the diet overlap is even lower as the charr predominantly feed on G. lacustris, whereas the trout mainly prey upon small Arctic charr. Gammarus is an important macroinvertebrate prey for many fish species (MacNeil et al 1999), but it is also an important intermediate host for several parasite species, including the cestode Cyathocephalus truncatus that can parasitize both Arctic charr and brown trout (Amundsen et al 2003;Knudsen et al 2008). This cestode can manipulate the behaviour of their Gammarus hosts in order to increase transmission rates (Knudsen et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Based on general dietary niches of charr and trout in sympatry (Nilsson, 1963;Langeland et al, 1991;Knudsen et al, 2008;Eloranta et al, 2013), we expected the transmission routes and the resulting infection patterns of two Diphyllobothrium species to differ between the fish species. The observed differences in Diphyllobothrium infections largely confirmed the expected copepod transmission route in charr and the piscivorous transmission route in trout.…”
Section: Discussionmentioning
confidence: 99%
“…This niche segregation may be reflected in the parasite communities of these two salmonids. Knudsen et al (2008) found that charr had more copepod-transmitted parasites than did trout and related this to charr feeding more often on zooplankton compared to trout.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations